2015
DOI: 10.14310/horm.2002.1586
|View full text |Cite
|
Sign up to set email alerts
|

A novel mutation of the calcium-sensing receptor gene in a Greek family from Nisyros

Abstract: We hereby report the identification of a novel heterozygous loss-of-function mutation of the CASR gene in a Greek family from Nisyros island. Functional studies are needed to clarify the exact role of this mutation in CASR activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…As these mutations usually lead to a severely truncated protein, one would expect to result in a more severe phenotype. However, in most of the reported cases, patients feature typical findings with mildly elevated Ca 2+ (16,17) as was also observed in our case and her father as well as in the patients from Nisyros (11). Previous research has suggested that alterations caused by specific mutations depend on the location of the substituted amino acid in one of the critical regions for ligand binding, receptor trafficking, and signal transmission but not on the extend of the defect (13).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…As these mutations usually lead to a severely truncated protein, one would expect to result in a more severe phenotype. However, in most of the reported cases, patients feature typical findings with mildly elevated Ca 2+ (16,17) as was also observed in our case and her father as well as in the patients from Nisyros (11). Previous research has suggested that alterations caused by specific mutations depend on the location of the substituted amino acid in one of the critical regions for ligand binding, receptor trafficking, and signal transmission but not on the extend of the defect (13).…”
Section: Discussionsupporting
confidence: 83%
“…The genetic change was located in exon 4 of the CaSR gene and resulted in a new reading frame and theoretically, in a shorter CaSR protein. The same genetic change has been recently described in an adult patient with mild hypercalcemia and her two siblings originating from a Greek island (Nisyros) (11), however a functional assay was not performed to clarify the functional impact. No common ancestry is known between our patient and the patient from Nisyros.…”
Section: Discussionmentioning
confidence: 87%
“…4 To date, more than 200 CaSR FHH-related mutations have been identified worldwide (online database available at http://www.casrdb.mcgill.ca). 5 Most mutations are missense and nonsense mutations, but deletions, insertions and splicing mutations have also been documented. The majority are localized in exons 3 and 4.…”
Section: Discussionmentioning
confidence: 99%